Inovatif di Tengah-Tengah Tuntutan Kerja: Apakah Sumber Daya Pekerjaan Berperan Sebagai Moderator? - Masita, Danny; Suyasa, P. Tommy Y. S. (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2025)
One of the efforts to improve public services is by enhancing the capacity and quality of civil servants (ASN). In this regard, Widyaiswara plays a crucial role as the front line in conducting education and training. Widyaiswara is required to deliver knowledge in an innovative manner. Through innovative behavior, Widyaiswara is expected to make learning more engaging, enjoyable, and effective for trainees. This study examines the role of job resources as a moderator between job demands and innovative behavior in Widyaiswara. The study involved 101 participants, with the majority (51.5%) being male. The instrument used to measure innovative work behavior was the Innovative Behavior Scale, while job demands and job resources were measured using the Job Demand-Resource (JD-R) Scale. The results indicate that job resources function as a moderator. Among participants with low job resources, job demands had no effect on increasing or decreasing innovative work behavior. However, among participants with high job resources, job demands actually contributed to an increase in innovative work behavior